(untitled) (Global Journal of Science Frontier Research, 2018)
This work examines the Relative Efficiency (RE) of some selected Randomized Complete Block Designs (RCBD).The efficiency of the selected designs showed that design B was the most preferable having Mean Square Error of 6.14, followed by design C with Mean Square Error of 9.11 and design A with Mean Square Error of 18.08. The results from the pair-wise relative efficiency of the selected designs show that RE(B,A) = 0.34 with the smallest relative efficiency value and RE(A,B) = 2.94 with the largest relative efficiency value. We recommended design B as the best design for this particular problem since its mean square error remains the smallest.